The tower and the bridge : the new art of structural engineering - Billington, David P., 1927-2018 (Princeton science library., 2022)
An essential exploration of the engineering aesthetics of celebrated structures from long-span bridges to high-rise buildingsWhat do structures such as the Eiffel Tower, the Brooklyn Bridge, and the concrete roofs of Pier Luigi Nervi have in common? According to The Tower and the Bridge, all are striking examples of structural art, an exciting area distinct from either architecture or machine design. Aided by stunning photographs, David Billington discusses the technical concerns and artistic principles underpinning the well-known projects of leading structural engineer-artists, including Othmar Ammann, Félix Candela, Gustave Eiffel, Fazlur Khan, Robert Maillart, John Roebling, and many others. A classic work, The Tower and the Bridge introduces readers to the fundamental aesthetics of engineering.